Causality Validation of Three Marketing Mix Components and Interest in Smartphone Purchase Decisions - Tri Cicik Wijayanti; Rahmawati Rahmawati; Muh. Alvianto Putra Arizandi Sadarrudin; Johan Johan; Dio Caisar Darma (Jurnal Sosioteknologi, 2022)
The field of technology has experienced phenomenal growth. Moreover, the evolutionof cellphones has become a major draw for customers. The aim of this study is tovalidate the effect of marketing mix components and interest in purchasing decisions forSamsung brand smartphones in the Tambaksari District (Surabaya City). A total of 498informants were recruited and interviewed for data collection on pricing, promotions,distributions, interests, and purchasing decisions at cellular kiosks and electronic stores.After the data were collected, they were analyzed using the multiple linear regressionmethod. The model feasibility procedure concluded that all seven hypotheses wereaccepted (p<0.05). In the direct effect, any increase in price, promotion, distribution,and interest can increase purchasing decisions. From the indirect effect, it is evidentthat interest is a consistent mediator in increasing its influence on price, promotion,and distribution on purchasing decisions. The marketing channel applied by the sellerinfluences consumer decisions through interest. This study’s approach should thereforebe developed through constructive consumer attention.